2015
DOI: 10.1021/acs.analchem.5b01764
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore-Based Electrical and Label-Free Sensing of Enzyme Activity in Blood Serum

Abstract: A generic strategy to expand the analytical scope of electrical nanopore sensing is presented. We specifically and electrically detect the activity of a diagnostically relevant hydrolytic enzyme and remove the analytically harmful interference from the biochemically complex sample matrix of blood serum. Our strategy is demonstrated at the example of the renin protease which is involved in regulation of blood pressure. The analysis scheme exploits a new approach to reduce sample complexity while generating a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…It should be noted that, one of the challenges to analyze clinical samples using the protein nanopore sensor is that the amphiphilic proteins in serum samples might disturb the lipid bilayer 34 using the vertical design used in this work, although it has been successfully used in other horizontal conducting chambers. 24 One feasible approach to overcome this difficulty is to use spin-columns to remove interfering blood serum components 46 . In our previous work, we found that by incubating mock serum samples with peptide substrates, and then analyzing the mixture solution using the protein nanopore sensor, we could sensitively determine the protease activity in the serum within minutes, thus overcoming the lipid bilayer’s short life-time limitation 31 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that, one of the challenges to analyze clinical samples using the protein nanopore sensor is that the amphiphilic proteins in serum samples might disturb the lipid bilayer 34 using the vertical design used in this work, although it has been successfully used in other horizontal conducting chambers. 24 One feasible approach to overcome this difficulty is to use spin-columns to remove interfering blood serum components 46 . In our previous work, we found that by incubating mock serum samples with peptide substrates, and then analyzing the mixture solution using the protein nanopore sensor, we could sensitively determine the protease activity in the serum within minutes, thus overcoming the lipid bilayer’s short life-time limitation 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Pioneering studies were devoted to the dynamics of peptides transport 9 , 10 , 13 , 14 , 16 , 30 , and then to the dynamics of unfolded proteins transport 18 , 31 , 48 through the nanopore. Others studies focused on protein-antibodies complex 32 , 41 , 42 , on intrinsically disordered proteins 49 , on enzymatic reactions 15 , 17 , 23 , 60 , 61 and on the aggregation of amyloidogenic peptides 36 , 47 , 55 . The unfolding of proteins was investigated, either in the presence of an unfolding agent 12 , 31 , 44 , or by varying temperature 24 , or with an electrical force 50 , 62 , or with a molecular motor such as an unfoldase 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Indirect detection of proteins via α-HL pores has been reported previously. 38, 41, 45, 142 In one approach, the activity of a protein enzyme is measured by monitoring the ion current modulations that occur due to protease–substrate reactions. In the absence of protease, translocation of intact peptide substrate molecules through a nanopore will produce one type of event.…”
Section: Biological Nanoporesmentioning
confidence: 99%